2016
DOI: 10.1016/j.envpol.2016.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress-induced toxicity of CuO nanoparticles and related toxicogenomic responses in Arabidopsis thaliana

Abstract: Microarray analysis of toxicogenomic effects of CuO NPs on Arabidopsis thaliana was conducted. Arabidopsis growth was significantly inhibited by CuO NPs (10 and 20 mg/L). CuO NPs (10 and 20 mg/L) caused significant root damage after short-time (0-2 h) exposure while their corresponding Cu(2+) ions (0.80 and 1.35 mg/L) did not show any root damage. After longer exposure times (1 and 2 days), Cu(2+) ions induced obvious root damage, indicating that released Cu(2+) ions from CuO NPs contributed partial toxicity d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(44 citation statements)
references
References 48 publications
(48 reference statements)
2
41
0
1
Order By: Relevance
“…ZnO-NPs has been reported to affect the soil microbial metabolism and reduce the numbers of the nutrient fixing bacteria such as the azotobacter, and P-and K-solubilizing bacteria [130,162]. CuO NPs are also reported to inhibit the root growth of wheat plants [163,164]. Copper nanoparticles can affect the photosynthetic, respiratory and growth processes of the plant at higher concentration and would pose dangers on humans when such crops are consumed.…”
Section: Biosafety Of Nanomaterials In Sustainable Agriculturementioning
confidence: 99%
“…ZnO-NPs has been reported to affect the soil microbial metabolism and reduce the numbers of the nutrient fixing bacteria such as the azotobacter, and P-and K-solubilizing bacteria [130,162]. CuO NPs are also reported to inhibit the root growth of wheat plants [163,164]. Copper nanoparticles can affect the photosynthetic, respiratory and growth processes of the plant at higher concentration and would pose dangers on humans when such crops are consumed.…”
Section: Biosafety Of Nanomaterials In Sustainable Agriculturementioning
confidence: 99%
“…Hence it can be reasoned that the excess production of ROS may result in secretion of EGF which in turn results in TNF production that prompts early production of IL-8 a change in the physiology of the cell namely, a decrease in oxygen levels due to ischemia/hypoxia will cause late induction of IL-8 that leads to activation of NF-KB pathway ( Table 4). The released copper ionic species is also considered to be the cause of CuO NPs-induced toxicity (Tang et al, 2016). Surface-released copper ions primarily affect cell membrane integrity.…”
Section: Mechanism For Cuo Nps-induced Toxicitymentioning
confidence: 99%
“…Growth inhibition was observed when Bacillus thuringiensis (Bt)-transgenic cotton was exposed to SiO 2 NPs (Le Van et al 2014). When wheat plants were grown in a sand matrix, CuO NPs inhibited their growth and changed the structure of the roots (Dimkpa et al 2012;Tang et al 2016). Shaw and Hossain (2013) showed that CuO NPs significantly reduced the fresh weights and root length of Arabidopsis seedlings, and the germination rate and biomass of rice seeds.…”
Section: Effect Of Nps On Plant Physiological Indicesmentioning
confidence: 99%